AMP-Activated Protein Kinase Signalling - Neumann, Dietbert; Viollet, Benoit (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Starting from a kinase of interest, AMP-activated protein kinase (AMPK) has gone far beyond an average biomolecule. Being expressed in all mammalian cell types and probably having a counterpart in every eukaryotic cell, AMPK has attracted interest in virtually all areas of biological research. Structural and biophysical insights have greatly contributed to a molecular understanding of this kinase. From good old protein biochemistry to modern approaches, such as systems biology and advanced microscopy, all disciplines have provided important information. Thus, multiple links to cellular events and subcellular localizations have been established. Moreover, the crucial involvement of AMPK in human health and disease has been evidenced. AMPK accordingly has moved from an interesting enzyme to a pharmacological target. However, despite our extensive current knowledge about AMPK, the growing community is busier than ever. This book provides a snapshot of recent and current AMPK research with an emphasis on work providing molecular insight, including but not limited to novel physiological and pathological functions, or regulatory mechanisms. Up-to-date reviews and research articles are included.